PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH TENTANG ORGANISASI SEKOLAH: Studi Kasus SMP Negeri 2 Jakenan - SUKATI , SUKATI (2011)
The school principal is often faced with complex problems. These problems demand solution quickly and accurately. School principals are required to have the ability to consider and make decisions carefully, including on SMP Negeri 2 Jakenan. The focus of this research is how the characteristics of personal/team in decision-making, decision-making process characteristics, and characteristics of the decision of school principals in school organization SMP Negeri 2 Jakenan? The purpose of this study was to describe the characteristics of personal/team in decision- making, decision-making process characteristics, and characteristics of the decision of the principal in school organization SMP Negeri 2 Jakenan This study uses qualitative research carried out in SMP Negeri 2 Jakenan. This research data in the form of words and actions received from principals and teachers / staff. Data were collected by interview technique, observation, and documentation. Data were analyzed using a single site. Characteristics of personal/team principal decision-makers are competence, rigor, seriousness, commitment of each person, and able to keep secret. Characteristics of decision-making process are (1) identify problems that occur at school, (2) made it a priority to be solved first, (3) analyze the problem to find the cause of the problem, (4) sets targets to be achieved in these solutions, (5) developed several ways (alternatives) to achieve it, (6) selecting one of the best alternatives, (7) implement the chosen alternative, and (8) evaluate the implementation of the decision. The decision making process can be performed by the principal, by personal/team appointed by the head of school, and in participation. Characteristics of the principal's decision are an instruction, innovation, and solutions. Because the decision can be made by personal/team, the principal should choose that meet the personal characteristics; documenting data, information, facts, or celebration of a regular basis to the decision-making materials; take decisions varied.